β-Amyloid or its precursor protein is found in epithelial cells of the small intestine and is stimulated by high-fat feeding - Galloway, Susan; Jian, Le; Johnsen, R.; Chew, Stewart; Mamo, John (Elsevier Inc, 2007)
In Alzheimer's disease (AD), β-amyloid (Aβ) is deposited in extracellular matrices, initiating an inflammatory response and compromising cellular integrity. Epidemiological evidence and studies in animal models provide strong evidence that high-saturated-fat and/or cholesterol-rich diets exacerbate cerebral amyloidosis, although the mechanisms for this are unclear. Aβ contains hydrophobic domains and is normally bound to lipid-associated chaperone proteins. In previous studies, we have put forward the notion that Aβ is a regulatory component of postprandial lipoproteins (i.e., chylomicrons) and that aberrations in kinetics may be a contributing risk factor for AD. To explore this further, in this study, we utilized an immunohistochemical approach to determine if Aβ or its precursor protein is expressed in epithelial cells of the small intestine — the site of chylomicron biogenesis. Wild-type mice were fed a low-fat or a high-fat dietary regime and sacrificed, and their small intestines were isolated. We found that, in mice fed low-fat chow, substantial Aβ/precursor protein was found exclusively in absorptive epithelial cells of the small intestine. In contrast, no Aβ/precursor protein was found in epithelial cells when mice were fasted for 65 h. In addition, we found that a high-fat feeding regime strongly stimulates epithelial cell Aβ/precursor protein concentration. Our findings are consistent with the notion that Aβ may serve as a regulatory apolipoprotein of postprandial lipoproteins.